Reverse logistic location problem for electrical and electronics equipment waste treatment facility - Fatma, E (Institut Teknologi Sepuluh Nopember, 2018)
Reverse logistics plays a significant role in reducing electrical and electronics equipment waste (e-waste) problem by returning some valuable or hazardous parts back to the distributor or producers. This paper implemented reverse logistics facility’s location problem to find the optimum location of e-waste treatment facilities. E-waste treatment facility location was determined in two phase. First, facility location model is developed to find the optimum location for e-waste treatment facility from the e-waste collecting points using K-means clustering and centre of gravity algorithm. Once the treatment facility location is decided, e-waste collection vehicle routing model is developed using saving matrix algorithm to minimize collecting distance. This paper was developed in three scenarios, based on e-waste collection problem in Jakarta. It is found that multi e-waste treatment facilities, gave the shortest collection distance compared to single and restricted area facility scenarios.